The Aquilegia JAGGED homolog promotes proliferation of adaxial cell types in both leaves and stems. Issue 2 (16th November 2016) - Min, Ya; Kramer, Elena M.
Summary: In order to explore the functional conservation of JAGGED, a key gene involved in the sculpting of lateral organs in several model species, we identified its ortholog AqJAG in the lower eudicot species Aquilegia coerulea . We analyzed the expression patterns of AqJAG in various tissues and developmental stages, and used RNAi‐based methods to generate knockdown phenotypes of AqJAG . AqJAG was strongly expressed in shoot apices, floral meristems, lateral root primordia and all lateral organ primordia. Silencing of AqJAG revealed a wide range of defects in the developing stems, leaves and flowers; strongest phenotypes include severe reduction of leaflet laminae due to a decrease in cell size and number, change of adaxial cell identity, outgrowth of laminar‐like tissue on the inflorescence stem, and early arrest of floral meristems and floral organ primordia. Our results indicate that AqJAG plays a critical role in controlling primordia initiation and distal growth of floral organs, and laminar development of leaflets. Most strikingly, we demonstrated that AqJAG disproportionally controls the behavior of cells with adaxial identity in vegetative tissues, providing evidence of how cell proliferation is controlled in an identity‐specific manner.